INTER-ROBOT DATA EXCHANGE FOR LOCOMOTION AND LOCALISATION - ZULKIFLI, MUHAMMAD AMIRUL ASHRAF (IRC, 2019)
This paper is about developing and study about the inter-robot data exchange for locomotion and localisation. Data exchange between robot is very important to ensure the accuracy and the integrity of the data received. To achieved reliable and accurate data transmission a sub-system is needed to create and parse the data properly that integrates with the communication protocol chosen that will be discuss in the next chapter. This project aiming to achieve a feasible communication sub-system that can create, and parse data mainly position, identity, and motion in an optimised format for data transmission. This project also aims to collect important data such as the performance, accuracy, and integrity of the data. The complete system will be tested in flat surface area to avoid error and gives the robot a stable platform to move. This project will cover the development of the communication sub-system and integrates it with selected communication protocol to provide a complete system for inter-robot communication projects as well as gathering data to analyse the performance of the robot, data accuracy, data integrity and scalability of the sub-system for future development. This project will have a system(robot) build using Arduino UNO as the microcontroller, motor driver, chassis design with motor, power source and motor encoder with sensor. The robot will be installed with a communication protocol selected and integrates it with the sub-system design developed beforehand. On the further chapter will discuss the test done in this project and discuss about the performance and the integrity of the data. The test that already done is data transmission test where the data is test to be sent and received using selected protocol and discuss about the result, another test is PWM test to check the performance of individual robot and the last test done to date is the straight line test where encoder distance ratio were calculated and used in each individual robot and discuss on the performance of the robot.